Decreased emergency department overcrowding by discharge lounge: A computer simulation study - Mehdi Nasr Isfahani (International Journal of Preventive Medicine, 2020)
Background: In the past decade, factors such as population growth, increased environmental incidents, and substance abuse have caused patient-overcrowding in emergency departments (EDs). Our main objective was to assess the effects of a discharge lounge on decreasing the patient waiting time and ED overcrowding by computer simulation. Methods: In this cross-sectional retrospective study, the statistical population consisted of 39264 persons referred to the ED of Al-Zahra Hospital. The sample size was calculated as 1275 through systematic random sampling at 99% confidence. To increase research accuracy, the number of patients was increased to 2515. Data were collected by standardized checklists and hospital information systems. Results: Mean waiting time for level 2 patients who left the ED against medical advice after completing the treatment was declined from 56 min to 44 min and before completing the treatment process from 80 min to 50 min. Average waiting time for level 3 patients for personal satisfaction after completing the treatment process decreased from 15 min to 13 min and before the completion of the treatment process from 67 min to 41 min; the number of discharged patients awaiting discharge was decreased at level 2 from 3 to 2 and at level 3 from 2 to 1. The number of patients waiting for admission at triage stations reduced from 44 to 39%, and the average number of patients discharged from emergency room was increased from 7 to 12. Conclusions: ED overcrowding is the hallmark of a mismatch between the availability of health care resources and patient demand for emergency care. Among major factors contributing to these situations are hindrances in patient flow and occupation of ED beds by nonurgent patients. The establishment of a discharge unit in the ED could be a practical solution to ED overcrowding.